2014
DOI: 10.1007/s10334-014-0464-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in the response of leg muscle cross-sectional area and water diffusivity measures to a period of supine rest

Abstract: Regardless of age, ADC values decreased with fluid shift associated with time spent supine, whereas CSA and FA were not affected. For leg muscle assessment in young and older women, DTI scanning protocols should consider the amount of time spent in a recumbent position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…If interested in these muscles, a set‐up with the calf suspended would be preferable (Lorbergs et al. ; Elzibak and Noseworthy ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If interested in these muscles, a set‐up with the calf suspended would be preferable (Lorbergs et al. ; Elzibak and Noseworthy ).…”
Section: Discussionmentioning
confidence: 99%
“…While this set-up is favorable for maximizing SNR in the posterior compartment, it also leads to deformation and compression of the gastrocnemius muscles. If interested in these muscles, a set-up with the calf suspended would be preferable (Lorbergs et al 2015;Elzibak and Noseworthy 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…The scan acquisition protocol is described elsewhere [28]. In brief, 30 contiguous axial proton density (PD)-weighted images (slice thickness = 4 mm; TE/TR = 30/2344 ms, field-of view (FOV) = 16 cm, matrix = 320 mm 9 320 mm, total scan time = 6 min 30 s) were acquired.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…In studies of muscle aging, fiber atrophy is of particular interest, with the decrease in muscle fiber size that occurs in sarcopenia contributing to the decline in muscle force generation (Lexell et al, 1983 ). However, only a few studies have investigated changes in diffusion metrics with age (Kermarrec et al, 2010 ; Lorbergs et al, 2015 ; Yanagisawa et al, 2009 ; Yoon et al, 2017 ), the most comprehensive being reported by Galbán et al ( 2007 ), Sinha et al ( 2015 ), and, more recently, Farrow et al ( 2021 ). However, these studies were conducted in small groups with a relatively narrow age range, or, in the case of the study by Sinha et al ( 2015 ), show data for only one sex.…”
Section: Introductionmentioning
confidence: 99%